Endothelial Dysfunction in Patients With Coronary Artery Disease: A Comparison of Three Frequently Reported Tests. (1st January 2002) - Monnink, Stefan H. J.; van Haelst, Paul L.; van Boven, Ad J.; Stroes, Erik S. G.; Tio, René A.; Plokker, Thijs W. M.; Smit, Andries J.; Veeger, Nic J. G. M.; Crijns, Harry J. G. M.; van Gilst, Wiek H.
Abstract : Background: Endothelial dysfunction is useful in predicting future cardiovascular disease. At present several tests are available to test endothelial function: coronary diameter response to acetylcholine, forearm bloodflow (FBF) response to acetylcholine, and brachial artery flow-mediated dilative (FMD) response to postischemic hyperemia. This study aimed to compare the three most frequently reported endothelial function tests. Methods: Twenty-eight patients (19 males and nine females, mean age 57 years) referred for diagnostic coronary angiography were considered for endothelial function measurement in the coronary artery as well as in the forearm by FBF and FMD. Results: Acetylcholine decreased the mean coronary diameter by 7.4% (SD 6.3%) and increased the mean FBF by 230% (SD 152%). Hyperemia increased the mean brachial diameter by 6.7% (SD 4.8%). The effect of acetylcholine on forearm resistance vessels was significantly related to the effect of acetylcholine on the coronary conduit vessels ( P =0.039). Nonetheless, FMD was not related to FBF nor to the coronary response. Conclusion: In patients with mild coronary endothelial dysfunction, forearm vasoreactivity is related to the coronary response, provided that the same stimulus is used.